Perancangan Dan Implementasi Penjualan Furniture Di Toko Furniture Gharsa Menggunakan Codeigniter - Celsia Enjelica; Faradika; Zulfahmi; Dio Prima Mulya (CV. ITTC INDONESIA, 2023)
Toko Furniture gharsa is a store that wants to take advantage of the potential of the internet to increase sales and reach of buyers. This journal discusses designing a sales website for Toko Furniture Gharsa using the CodeIgniter Framework. This research aims to facilitate the shopping process for consumers,in this design the author uses an object-oriented approach and utilizes the features provided by CodeIgniter to build an efficient and easy web,this article includes analysis of user and seller needs,system development to make it easier for buyer to check product design,with this website can expand customer reach in increasing sales.